Analisis Kesiapan Guru dalam Mengimplementasikan Kurikulum 2013 di PAUD - Melania Marsela Kongen; Petrus Redy Partus Jaya (Universitas Trunojoyo Madura, 2019)
This study was conducted to determine the extent of teacher readiness in implementing the 2013 Curriculum in PAUD. This type of research was a descriptive study with a qualitative approach. The research subjects were 21 teachers in Langke Rembong sub-district. Data collection techniques using interviews and questionnaires. The instrument used was interview guidelines and questionnaire items in the form of open questions. In this study, researchers examined the readiness of teachers related to the implementation of the 2013 Curriculum (K'13) in terms of Curriculum Structure, Guidelines for Detection of Children Growth, Learning Guidelines, Assessment Guidelines, and Educator Guidebooks. Teacher readiness is measured by the extent of the teacher's ability to implement the 2013 Curriculum in PAUD. Based on the findings related to five things in organizing the 2013 Curriculum in PAUD, it appears that administratively PAUD teachers are ready to implement the 2013 Curriculum in PAUD. However, practically the teachers still experience difficulties. These difficulties are related to the application of a scientific approach and the implementation of authentic assessments. In learning, teachers have difficulty designing activity themes and materials that encourage children to observe, ask questions, gather information, reason, and communicate. That is why, learning is more directed at drawing and coloring activities. In doing the assessment, the teacher has difficulty compiling data on the results of the daily assessment and compiling reports on child development. This difficulty occurs because most of the teachers are high school / vocational high school and non-PAUD undergraduate students